Efektivitas Rancangan dan Implementasi Modul Ajar pada Pembelajaran PKn Kelas IX di SMP Negeri 1 Samarinda - Dessy Kartika Sari; A. Hardoko; Marwiah Marwiah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to determine the effectiveness of the design and implementation of teaching modules in Class IX learning at SMP Negeri 1 Samarinda as a result of the teacher’s teaching module design which is a document containing the objectives, steps, media and assessment needed in implementing civics learning in class. Apart from that, in the effectiveness of the design and implementation of teaching modules in civics learning, teachers must design teaching modules before teaching in the classroom by designing them interestingly and creatively ti achieve the objectives of implementation plan made by the teacher and reflect on themselves to achieve goals. And teachers must be able to utilize technology in learning ehen implementing learning in class, implementing learning that guides, directs, direcst student in achieving learning goals. This research is descriptive research using a qualitative approach. Sources of research data include civics teachers and class IX students of SMP Negeri 1 Samarinda. Data collection uses observation, interviews and documentation. The data analysis technique is using data reduction, data presentation, data presentation and conclusions. Triangulation was carried out to explain the validity of the data using source interviews and techniques. So the research results shiw that the teaching module design created by the teacher is the teacher’s guidance and guidance before teaching and must be designed or designed in an attractive way to achieve learning objectives. Having an attractive teaching module design can increase educators understanding and activeness in learning and guide teachers in designing teaching and learning modules in accordance with the learning objectives to be achieved in the classroom learning process.